Using MultiSIM troubleshooting DC/AC circuits - Reeder, John (Thomson Delmar Learning, 2007)
Supplements basic DC/AC instruction and demonstrates how to troubleshoot faulty circuits using MultiSIM as the standard tool. This book enables readers to make measurements, determine faults, replace components, and test results using the same processes and techniques that would be used in an actual hardware lab.